Clinical Experience of Pemphigus Vulgaris in Georgian Patients - Matoshvili, Maia; Tophuria, Davit; Kakhniashvili, Inga; Benashvili, Levan (Caucasus Journal of Health Sciences and Public Health, 2016)
Background: Pemphigus vulgaris (PV) is an autoimmune bullous disorder characterized by autoantibodies directed against desmoglein 3. The aim of the study was to assess the clinical and histological profile and treatment outcomes in a consecutive group of patients with pemphigus vulgaris followed in our clinic. We performed a clinical based study on 26 patients with pemphigus vulgaris seen between 2012 and 2015 years. The gender of patients was 18 female (69%) and 8 male (31%). The mean age of onset of PV was 45 years. The areas of involvement: 26 (100%) oral, 19 (73%) skin, 7 (26.9%) genital, 6 (23.1%) nasal, <20% pharyngeal, ocular, laryngeal, anal, or esophageal involvement (in descending order). 28 (90.3%) of 31 biopsies in 25 patients were consistent with PV. 21(80.8%) achieved complete remission with a median duration of 18 months. The medications used were prednisone, dapsone, azathioprine and for locally treatment topical corticosteroids, cyclophosphamide, oral methyl prednisolone and tetracycline. The median time needed to achieve complete remission after the first visit was 9 months. Results: The majority of PV patients were females. Middle age was the time at which the disease most often presented. The oral cavity was involved in all cases over the course of the disease. Histological examination of biopsy material confirmed the diagnosis of PV most reliably. Complete remission was achieved in the majority of patients using combinations of medications.